An Upper Lip Swelling: A Case Report, Differential Diagnosis and Review of Literature - Bhattacharya, Preeti Tomar; Pal, Sumona; Sinha, Rupam; Misra, Mayukh; Bhattacharya, Arka (Journal of Orofacial Research, 2013)
Pleomorphic adenoma is the most common tumor of the salivary glands. About 90% of these tumors occur in the parotid gland and 10% in the minor salivary glands. The most common site for pleomorphic adenoma of the minor salivary glands is the palate followed by upper lip. Surgical removal with adequate margins is the principal treatment. Due to its microscopicprojections, this tumor requires a wide resection to avoid recurrence. We report a case of pleomorphic adenoma in the upper lip of an elderly female with emphasis on differentialdiagnosis and relevant review of literature.